Challenges and issues in knowledge management - Buono, Anthony F.; Poulfelt, Flemming (Research in management consulting., 2005)
Challenges and Issues in Knowledge Management - the fifth volume in the Research on Management Consulting series - presents sixteen chapters that explore these various perspectives, focusing on knowledge management within the context of the management consulting industry, the dynamics associated with knowledge sharing and dissemination, methodological approaches to studying knowledge in organizations, and reflections on knowledge management and management consulting. As the chapters underscore, it is important to ensure that KM initiatives are aligned with the needs of the organization and its members, that the KM system is 'owned' by organizational members with particular emphasis on executive sponsorship and team member acceptance, and that it be understood as an ongoing process rather than simply another management objective or faddish consulting tool. The focus, therefore, should be on how knowledge processes can be facilitated, leveraged and utilized in organizational value creation.